Proximity-driven site-specific and covalent labeling of proteins with a TexasRed fluorophore Reacting (ReacTR) Peptide Tag - Sünbül, Murat; Jäschke, Andres (Proximity labeling, 2019)
It is of vital importance to visualize proteins in living cells noninvasively in order to elucidate their functions. Here, we describe a fast, efficient, and one-step covalent protein labeling method utilizing a small peptide tag called TR512, which was previously engineered to bind to TexasRed fluorophore by phage display. To covalently label proteins with TexasRed fluorophore, proteins of interest (POI) were fused to a reactive TR512 (ReacTR) tag carrying two cysteine residues. Upon addition of TexasRed fluorophore conjugated to N-α-chloroacetamide, a cysteine group of the ReacTR tag rapidly reacts with the electrophilic N-α-chloroacetamide gs uroup due to the proximity effect by forming a covalent bond between the fluorophore and ReacTR tag. Our approach uses a small peptide tag and a small-molecule fluorophore for labeling; thereby minimal perturbation on the function and dynamics of the POI is expected.
Gesehen am 16.04.2020